1987
DOI: 10.7901/2169-3358-1987-1-459
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Brittany Coastal Marshes in the Eight Years Following the Amoco Cadiz Incident

Abstract: The salt marshes on the Brittany coast of France have undergone a number of changes and have been influenced by man-made and natural factors since the Amoco Cadiz spill of March 1978. This work catalogs the ecological changes which have occurred over the past eight years and presents original data on the present state of these marshes. The recovery of Brittany coastal marshes began following cleanup operations which were often damaging to marsh and marsh substrate. The physical and toxicological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…The patchiness of the oiling and the heterogeneity of the spatial and temporal aspects of return to background concentrations, or nondetectable concentrations for petroleum hydrocarbon in the marsh sediments, is consistent with results of studies of previous spills that oiled marshes or mangroves (e.g., Teal et al, 1978;Burns and Teal, 1979;NRC, 1985NRC, , 2003Baca et al, 1987;Burns et al, 1993Burns et al, , 1994Reddy et al, 2002;Bejarano and Michel, 2010).…”
Section: Marshessupporting
confidence: 84%
“…The patchiness of the oiling and the heterogeneity of the spatial and temporal aspects of return to background concentrations, or nondetectable concentrations for petroleum hydrocarbon in the marsh sediments, is consistent with results of studies of previous spills that oiled marshes or mangroves (e.g., Teal et al, 1978;Burns and Teal, 1979;NRC, 1985NRC, , 2003Baca et al, 1987;Burns et al, 1993Burns et al, , 1994Reddy et al, 2002;Bejarano and Michel, 2010).…”
Section: Marshessupporting
confidence: 84%
“…Once oil penetrates the sediment, the recovery to reference conditions may take 3-4 years (Alexander and Webb 1987, Mendelssohn et al 1993, Hester and Mendelssohn 2000 or longer (Bergen et al 2000, Michel et al 2009. Under extreme circumstances, recovery may never occur due to sediment removal (Baca et al 1987, Gilfillan et al 1995 or accelerated erosion after vegetation morality . Even after plants resume growth, oil may continue to adversely affect soil microbial functions in coastal wetlands (Burns andTeal 1979, Pezeshki et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies of the impact of DWH on vegetation, soil parameters, microbes, benthic microalgae, and infauna ( Fleeger et al, 2015 ; Fleeger et al, 2017 ; Husseneder, Donaldson & Foil, 2016 ; Lin & Mendelssohn, 2012 ; Lin et al, 2016 ; McCall & Pennings, 2012 ; Silliman et al, 2012 ; Zengel et al, 2015 ; Zengel et al, 2016a ; Zengel et al, 2016b ) have been conducted in northern Barataria Bay. These and other studies have shown that plant species respond differently to oiling ( Alexander & Webb, 1987 ; Baca, Lankford & Gundlach, 1987 ; Culbertson et al, 2008 ; DeLaune et al, 2003 ; Hester & Mendelssohn, 2000 ; Hoff, Shigenaka & Henry, 1993 ; Lin & Mendelssohn, 1996 ; Lin & Mendelssohn, 1998 ; Lin & Mendelssohn, 2008 ; Lin & Mendelssohn, 2009 ; Lin et al, 2002 ; Mendelssohn et al, 1990 ; Mendelssohn et al, 2012 ; Michel & Rutherford, 2014 ; Pezeshki et al, 2000 ; Zengel et al, 2015 ; Zengel et al, 2016a ; Zengel et al, 2016b ). DWH impacts on vegetation include reductions in photosynthesis, transpiration, shoot height, stem density, and above- and belowground biomass.…”
Section: Introductionmentioning
confidence: 66%